Methods of phylogenetic transformations of cells and tissue systems of vertebrates (Eurasian Journal of Ecology, 2016)
This article discusses the different approaches to the analysis of morphological and functional foundations of evolutionary theory: tihogenetic concept leading role in the evolution of external factors (classical Darwinism) and nomogenetic concept of the primacy of own properties the living in the evolutionary process. Also provides a brief overview the epigenetic theory of evolution based on the recognition a fixed number of holistic living organismphenotypic reactions to external influences (stable morphoses set). It analyzes the applicability of the classical principles (types) of phylogenetic morphofunctional organs changes at the tissular and cellular levels. Examined 10 major types of morphofunctional evolution of tissue systems and cells on the example organs biodynamics of external gas exchange among the Tetrapoda.
Keywords: the tihogenetic and nomogenetic theories of evolution; epigenetic theory of evolution; selective and stabilizing selection; morphofunctional evolution; stable morphoses.